(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract This study aims to identify the repercussions of the Corona pandemic (Covid 19) and its impact on the educational and psychological functions of the Omani family from the point of view of a number of fathers and mothers. Drive for a group of fathers and mothers, some of whom work in the government sector and others are mothers enrolled in graduate studies programs at the university, their ages range between (30-50 years) totally (28) mothers and fathers: 22 mothers and 6 fathers. The results showed that the repercussions of the transformation of e-learning, home quarantine, social distancing, and the challenges associated with them were among the most frequent responses that posed a real challenge to the Omani family in performing the educational function. On the other hand, the responses concern the children’s educational future, fear and anxiety about acquiring negative behavioral patterns for the son such as addiction to social media and the decrease in the children’s motivation towards education topped the list: lack of responsibility in performing their academic tasks, anxiety, and fear of injury, fear for the elderly, feeling of psychological isolation, difficulty finding recreational alternatives for children, challenges associated with the performance of the family’s psychological function were observed. Based on these results, the researcher suggested including a number of psychological, cognitive, family-related, and behavioral guiding techniques to enhance the skills of fathers and mothers in dealing with family challenges and crises, in general, and the educational and psychological function, in particular.